A rodent model of enhanced anticipation of positive events: sex-specific modifications in cognitive bias and emotional resilience - Hartvigsen, Sarah C.; Hooper, Megan; Harding, Olivia; Barringer, Evelyn; DiLandro, Isabel; Narayanan, Aditya; Crockett, Brendan; Shatalov, Yulia; Tomé, Isabella; Luby, Paean; Wixted, Braden; Kent, Molly; et al. (Frontiers in Behavioral Neuroscience, 2025)
While it is known that chronic unpredictable stress and negative events adversely affect neurobiological outcomes, much less is known regarding the neurobiological impact of positive emotions such as chronic anticipation of appetitive events. From a translational perspective, an enhanced understanding of the impact of extended exposure to positive emotions may provide novel insights into effective non-pharmacological, behavior-based approaches to enhance mental resilience. Here, we investigate a novel rodent model of chronic Unpredictable Positive Event Response (UPER) training in male and female Long Evans rats to examine behavioral, neural, and endocrine effects of enhanced anticipation of positive events. Rats were exposed to either 3 weeks of daily, randomly administered, cued positive events (UPER training) or exposure to the same positive events administered at the same time (i.e., in a predictable manner) each day to control for anticipation (Enriched Control Training; ENR). Following UPER and ENR training, rats were assessed for cognitive bias, exploratory behaviors, and persistence in a Cognitive Bias Assessment paradigm, Novelty-Suppressed Feeding Task, and an Unattainable Puzzle Reward Task, respectively. In the Cognitive Bias Assessment, a trend for UPER-trained males to respond with an optimistic bias was observed. A main effect of training was observed in the Unattainable Puzzle Reward Task, with UPER-trained rats exhibiting reduced latency to interact with the novel object. A sex-dependent latency to consume a food reward in a Novelty-Suppressed Feeding Task was also seen. Focusing on fecal corticosterone metabolite (FCM) levels following anticipation-enhanced versus anticipation-minimized training, UPER-trained rats exhibited a trend for lower levels than ENR-trained rats. No c-fos activation differences were observed between the groups. Overall, these preliminary findings suggest that anticipation for positive events may have sex-specific effects on emotional responses to uncertain events. Accordingly, further research may determine relevance of this model in preclinical models of psychiatric diseases.